2014
DOI: 10.18632/oncoscience.74
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 as a multifunctional therapeutic target to prevent and combat cancer metastasis

Abstract: ABSTRACT:Metastatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…[64]. Previously dormant cells give rise to an increased number of CSCs in cell culture [31] (Fig. 2A).…”
Section: Csc Quiescencementioning
confidence: 95%
See 4 more Smart Citations
“…[64]. Previously dormant cells give rise to an increased number of CSCs in cell culture [31] (Fig. 2A).…”
Section: Csc Quiescencementioning
confidence: 95%
“…Some of them are closely related to bioenergetic stress and cancer cell metabolism (CD133, ALDH1) [26][27][28], and others are expressed to differing degrees at different stages of the cell cycle [29,30]. Despite such limitations, it has been shown that carcinoma cells overexpress CD133, CD44, ALDH1, Bmi-1 and other currently known CSC markers, and that they are resistant to ionizing radiation and chemotherapeutic drugs [28,29,31,32]. Most reports on the molecular patterns of CSCs are based on findings in carcinoma cells positive for any of the above CSC markers.…”
Section: Csc Concept and Response To Radiation Induced Dna Damagementioning
confidence: 99%
See 3 more Smart Citations